Congruence of Home, Social and Sex Neighborhoods among Men Who Have Sex with Men, NYCM2M Study - Koblin, Beryl A. (J Urban Health, 2016)
Substantial literature demonstrates the influence of the neighborhood environment on health behaviors and outcomes. But limited research examines on how gay and bisexual men experience and exist in various geographic and virtual spaces and how this relates to their sexual behavior. New York City Men 2 Men (NYCM2M) was a cross-sectional study designed to identify neighborhood-level characteristics within the urban environment that influence sexual risk behaviors, substance use, and depression among men who have sex with men (MSM) living in NYC. The sample was recruited using a modified venue-based time-space sampling methodology and through select websites and mobile applications. Whether key neighborhoods of human activity, where a participant resided (termed home), socialized (termed social), or had sex most often (termed sex), were the same or different was evaluated. “Congruence” (or the sameness) of home, social, and most often sex neighborhood was reported by 17 % of men, while 30 % reported that none of their neighborhoods were the same. The largest group of men (39 %) reported that their home and sex neighborhoods were the same but their social neighborhood was different while 10 % reported that their home neighborhood was different than their social and sex neighborhood; 5 % men reported same home and social neighborhoods with a different sex neighborhood. Complete neighborhood incongruence was highest among men who were Black and/or Latino, had lower education and personal income levels, and had greater financial insecurity. In adjusted analysis, serodiscordant condomless anal intercourse and condomless anal intercourse with partners from the Internet or mobile applications were significantly associated with having the same social and sex (but not home) neighborhoods. Understanding the complexity of how different spaces and places relate to the health and sexual behavior of MSM is essential for focusing interventions to best reach various populations of interest.